Genetic Line by Environment Interaction on Rainbow Trout Growth and Processing Traits. (3rd April 2017) - Cleveland, Beth M.; Leeds, Timothy D.; Rexroad III, Caird E.; Summerfelt, Steven T.; Good, Christopher M.; Davidson, John W.; May, Travis; Crouse, Curtis; Wolters, William R.; Plemmons, Bryan; Kenney, P. Brett
Abstract: Genetic line-by-environment (G×E) interactions were determined for growth and processing traits of five genetic lines of Rainbow Trout Oncorhynchus mykiss reared in four environments. Genetic lines included (1) a mixed pool of 109 families selectively bred for improved growth (Growth Line) at the U.S. Department of Agriculture (USDA) National Center for Cool and Cold Water Aquaculture (NCCCWA; Kearneysville, West Virginia), (2) a mixed pool of 52 randomly bred families (Synthetic Control) and fish from three commercial sources, identified as (3) Commercial A, (4) Commercial B, and (5) Commercial C. Two study locations (NCCCWA and The Conservation Fund's Freshwater Institute [FI], Shepherdstown, West Virginia) contained all five genetic lines of fish while the remaining two sites (USDA National Cold Water Marine Aquaculture Center, Franklin, Maine, and Casta Line Trout Farm, Goshen, Virginia) contained only the Growth Line and Commercial A fish. Fish were PIT-tagged and allowed to comingle at all locations except at Casta Line where Growth Line and Commercial A fish were stocked into separate raceway sections. Performance of the Growth Line and Commercial A fish across all locations were used to detect G×E interactions. Body weight of the Growth Line fish was similar to or exceeded that of Commercial A fish, and the G×E interaction for growth was beyond 1 year of age ( P < 0.05). A G×E interaction occurred for condition factor (CF), and the Growth Line fish generally exhibited a higher CF than did the Commercial A fish. There was a G×E interaction for fillet yield in fish harvested at 500 g or less, with no G×E effect for butterfly yield, viscera yield, or final mortality. Data from all five genetic lines at NCCCWA and FI indicate that large differences in genetic potential for growth and processing traits are not significantly affected by G×E interactions Received February 3, 2016; accepted December 2, 2016 Published online February 16, 2017